2017
DOI: 10.1007/s40641-017-0084-8
|View full text |Cite
|
Sign up to set email alerts
|

Greenland Ice Sheet Surface Mass Loss: Recent Developments in Observation and Modeling

Abstract: Surface processes currently dominate Greenland ice sheet (GrIS) mass loss. We review recent developments in the observation and modeling of GrIS surface mass balance (SMB), published after the July 2012 deadline for the Fifth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC AR5). Since IPCC AR5, our understanding of GrIS SMB has further improved, but new observational and model studies have also revealed that temporal and spatial variability of many processes are still poorly quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 112 publications
(133 reference statements)
1
94
0
1
Order By: Relevance
“…Our findings generally support the Woollings et al (2008) hypothesis that negative NAO arises from Greenland blocking and that positive NAO mainly represents the absence of blocking (rather than "anti-blocking" or negative GBI conditions). This is also in agreement with the results of Davini et al (2012b), who found that the first empirical orthogonal function of the 500 hPa geopotential height over Europe and the North Atlantic did not resemble the NAO for GBI cases but more closely resembled an East Atlantic circulation pattern (e.g., Hall et al, 2015;Hall and Hanna, 2018) and that North Atlantic jet variability was then no longer related to Greenland blocking changes. Also in support of our findings that high-GBI and low-NAO events do not always align, Rimbu et al (2017) found that stableisotope variations in GrIS cores are more closely related to measures of Atlantic-European/Greenland blocking than the NAO index.…”
Section: Discussion/summarysupporting
confidence: 92%
“…Our findings generally support the Woollings et al (2008) hypothesis that negative NAO arises from Greenland blocking and that positive NAO mainly represents the absence of blocking (rather than "anti-blocking" or negative GBI conditions). This is also in agreement with the results of Davini et al (2012b), who found that the first empirical orthogonal function of the 500 hPa geopotential height over Europe and the North Atlantic did not resemble the NAO for GBI cases but more closely resembled an East Atlantic circulation pattern (e.g., Hall et al, 2015;Hall and Hanna, 2018) and that North Atlantic jet variability was then no longer related to Greenland blocking changes. Also in support of our findings that high-GBI and low-NAO events do not always align, Rimbu et al (2017) found that stableisotope variations in GrIS cores are more closely related to measures of Atlantic-European/Greenland blocking than the NAO index.…”
Section: Discussion/summarysupporting
confidence: 92%
“…Mass losses from ice discharge and negative surface mass balance (SMB—the difference between surface accumulation and ablation) were roughly equivalent prior to 2005. Since 2005 the SMB component of GrIS mass loss has exceeded the ice discharge component, and SMB is projected to dominate the GrIS contribution to global sea level rise during the twenty‐first century (Enderlin et al, ; Van den Broeke et al, ). The primary cause of the decreasing SMB trend is increasing melt during summer, as there has been no significant trend in precipitation over the GrIS during this time (Fettweis et al, ; Noël et al, ; Van As et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Over 20 million people currently reside on land potentially vulnerable to flooding from sea level rise within the United States (Strauss et al, 2015). Reducing the uncertainty in future sea level rise therefore is key to planning and adaptation.…”
Section: Introductionmentioning
confidence: 99%